Calculation of FC F for Be9C l35 molecules - Hsoun, Ashwaq (Iraqi Journal of Science, 2023)
Franck-Condon factors (FCF), which are proportional to peak intensities, were calculated as the square of the overlap between the initial and final state wavefunctions in order to calculate of molecule Be9Cl35 their overlap using numerical Integration for the vibrational band (′v =0 - 4) to (v″=0 –4) of the electronic transition A 2Π - Χ 2 Σ and by using an appropriate Potential for each of them .for vibrational ground and first excited states.this new vibrational level must be instantaneously compatible with the nuclear positions and momenta of the vibrational level of the molecule in the originating electronic state. In the semiclassical picture of vibrations (oscillations) of a simple harmonic oscillator, the necessary conditions can occur at the turning points, where the momentum is zero. This leads to, in general, an increase in the "allowed’’ vibronic transitions and hence greatly influences the observed spectrum. For all but the simplest models for the electronic potentials, one must resort to a numerical calculation of the observed spectrum.